Specific futsal training program can improve the physical performance of futsal players - Barbieri, Ricardo Augusto [UNESP] (2016)
Purpose: This study investigated the effects of 12-week of specific futsal training on body composition, oxygen uptake (VO2max), anaerobic capacity, and agility of male semi-professional futsal players. Methods: Thirteen athletes were subjected to a 12-week program of specific training for futsal with the external load of sessions prescribed from rated perceived exertion. VO2max, agility, anaerobic index, and body composition were assessed before and after the 12-week training program. Results: The main findings were that the 12-week training period was able to significantly reduce the fat percentage of body composition (−7.5 %) and to improve the agility (3.9 %), aerobic capacity (>7 %), and anaerobic index (6–25 %). Conclusions: Based on these results, it can be concluded that a 12-week program of specific training for futsal with the external load of sessions prescribed from rated perceived exertion can significantly improve the body composition, agility and aerobic and anaerobic capacity of semi-professional futsal players.